Olecranon fractures in children: treatment of a rare entity - Kalbitz, Miriam; Weber, Birte; Lackner, Ina; Beer, Meinrad; Pressmar, Jochen (European Journal of Trauma and Emergency Surgery, 2020)
Background: Olecranon fractures are a rare entity in children. The classification and treatment strategies are still discussed controversially. Methods: A retrospective chart review of all patients < 17 years admitted with an olecranon fracture at a Level I Trauma Center between 2005 and 2017 has been performed. 46 subjects were included. For classification of olecranon fractures in children the AO Pediatric Comprehensive Classification of Long Bone Fractures (AO-PCCF) was used. Fractures were classified along the fracture line, dislocation, joint involvement and affection of the apophysis. For statistical analysis, a comparison of two groups was performed using Student t test. One-way ANOVA and Tukey’s multiple comparison test was used to identify differences between more than two groups. For all analysis p ≤ 0.05 was considered statistically significant. Results: The mean age of the children was 8.5 years (2–16 years). Most children were treated with a conservative therapy (n = 29, 63.0%). 17 patients (36.9%) underwent osteosynthesis (plate or tension band wiring) of which three were initially treated with a conservative therapeutic approach. Children with operative treatment were significantly older compared to children treated conservatively. Interestingly, all patients with luxation were characterized by an oblique fracture line, one of them extraarticular, three intraarticular. Conclusion: Taken together, this study analyzed one of the largest selections of pediatric patients with olecranon fracture in regard to fracture type and treatment strategy. Based on the assumption that treatment strategies follow a fracture classification, a consistent classification method is needed which should take into account fracture morphology and localization, as considered by the AO-PCCF, and the dislocation as measured by Braque. Surgical treatment is needed in case of dislocation ≥ 5 mm, intra-articular fractures, instable fracture conditions caused by the fracture line, open fractures and the affection of the apophysis. Otherwise, the conservative treatment shows insufficient results in the elbow mobility. The reliable choice of treatments based on our classification was mirrored by the very low rate of conversion of treatment strategies. Level of evidence: Level III-retrospective comparative study.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Cerclage; Children; Elbow; Fracture; Olecranon; Percutaneous pinning; Tension band wiring